Elasticity Profile of Skin, Neuronal, Cardiac, and Skeletal Muscle Cells after Treatment with the Biofield Energy Healing-Based Proprietary Test Formulation - Mahendra, Kumar Trivedi; Alice, Branton; Dahryn, Trivedi; Snehasis, Jana (Journal of Biotechnology and Biomedical Science, 2021)
The present study aimed to evaluate the effect of the Trivedi Effect®- Biofield Energy Treated/Blessed Test formulation/item (TI) composed of minerals (magnesium, zinc, copper, calcium, selenium, and iron), vitamins (ascorbic acid, pyridoxine HCl, alpha tocopherol, cyanocobalamin, and cholecalciferol), Panax ginseng extract, CBD isolates, and β-carotene on elasticity of skin, heart, muscle, and neuronal cells in the H9C2 (rat cardiomyocytes), C2C12 (mouse myoblast cells), HaCaT (human keratinocytes), and SH-SY5Y (human neuroblastoma cells) cell line in DMEM medium. The test formulation constituents were divided into two parts; one section was defined as untreated test formulation (UT), while the other portion of test formulation received Biofield Energy Healing/Blessing Treatment (BT) by a renowned Biofield Energy Healer, Mr. Mahendra Kumar Trivedi. The test items were treated with Biofield Energy Healing/Blessing Treatment and divided as Biofield Energy Treated/Blessed (BT) and untreated (UT) test items. MTT data showed that the test formulation in various concentrations was found as safe and nontoxic in the tested concentrations with viability range from 73% to 307%. Young’s modulus (YM) is a measure of cell stiffness, a decrease in YM value indicates increase elasticity of the cells and vice-versa. YM in H9C2 cells were decreased by 9.6% and 66.1% in the BT-DMEM + UT-TI group at 0.1 and 1 µg/mL respectively, as compared with untreated test group. However, C2C21 cells showed increased YM by 443.9% at 1 µg/mL in the UT-DMEM + BT-TI group, while 869.6% increased YM in the BT-DMEM + UT-TI group at 1 µg/mL as compared with untreated test group. However, 314% increased YM was reported in the BT-DMEM + BT-TI group at 1 µg/mL as compared with the untreated test group. However, the value of YM was significantly decreased in the HaCaT cell line by 247.7% (at 1 µg/mL), 225.8% (at 0.1 µg/mL), and 97.9% (at 1 µg/mL) in the UT-DMEM + BT-TI, BT-DMEM + UT-TI, and BT-DMEM + BT-TI group respectively, as compared with the untreated group. In addition, YM was significantly decreased in the SH-SY5Y cell line by 92.6%, 18.1%, and 26.6% at 1 µg/mL in the UT-DMEM + BT-TI, BT-DMEM + UT-TI, and BT-DMEM + BT-TI group respectively, as compared with the untreated group. Overall, the results showed the significant decreased YM among the SH-SY5Y, HaCaT, and H9C2 cells, while it was increased in the C2C21 cell line. Thus, the mechanical properties of cells such as cellular function, including shape, motility, differentiation, division, and adhesion to its surrounding extracellular matrix were improved. Overall, it can be useful in many disease progressions with improved cellular elasticity and its associated complications/symptoms.
Keywords: Biofield Treatment; Elasticity; The Trivedi Effect®; SH-SY5Y; HaCaT; and H9C2; C2C12.